Prognostic impact of Interleukin-1 receptor antagonist in patients with documented coronary artery disease. (15th April 2018) - Schofer, Niklas; Ludwig, Sebastian; Rübsamen, Nicole; Schnabel, Renate; Lackner, Karl J.; Ruprecht, Hans J.; Bickel, Christoph; Landmesser, Ulf; Blankenberg, Stefan; Zeller, Tanja
Abstract: Background: IL-1β-mediated inflammation contributes to development and progression of coronary artery disease (CAD). We aimed to assess the prognostic impact of the inflammatory marker Interleukin-1 receptor antagonist (IL1-Ra), reflecting high IL-1β activity, in patients with documented CAD. Methods: IL-1Ra levels were determined in 1337 subjects of the Athero Gene study, a prospective cardiovascular registry comprising patients with CAD as detected by coronary angiography presenting with acute coronary syndrome (ACS) or stable angina. Median follow-up was 6.4 years. Results: Patients with IL1-Ra levels in the highest tertile presented more often with ACS (55% vs. 40% vs. 34%, p < 0.001), were more commonly treated with PCI (47% vs. 39% vs. 34%, p < 0.001), had lower left ventricular ejection fraction (LVEF) (61 ± 15% vs. 62 ± 15% vs. 65 ± 14%, p = 0.001) and higher hs-CRP levels (10.0 vs. 4.2 vs. 2.5 mg/L, p < 0.001). IL1-Ra levels at baseline were predictive for all-cause mortality in the total study cohort after adjustment for conventional cardiovascular risk factors, LVEF, hs-CRP and Troponin T (adjusted HR 1.45 (95% CI 1.16–1.82), p < 0.001). In a subgroup of patients with ACS, but not in those with stable angina, IL1-Ra was an independent predictor for cardiovascular mortality (ACS: adjusted HR 1.85 (95% CI 1.33–2.58), p < 0.001; stable angina: adjusted HR: 1.25 (95% CI 0.95–1.65), p = 0.11). Conclusion: IL1-Ra is an independent predictor for adverse outcome in patients with documented CAD, beyond the prognostic value of hs-CRP and Troponin T in particular in the setting of ACS. For CAD patients our finding might improve both, risk assessment in secondary prevention and patient selection for anti-inflammatory treatment. Highlights: High IL-1Ra levels are associated with ACS, poorer LVEF and need for PCI. IL-1Ra levels independently predict mortality in CAD patients. IL-1Ra levels show the strongest impact on adverse outcome in patients with ACS.